Analisis Komparasi Performa Metode Double Exponential Smoothing Tipe Holt Dan Double Moving Average Untuk Peramalan Jumlah Penduduk Miskin Di Provinsi Maluku - Kondo Lembang, Ferry; Makatita, Romy; Haumahu, Gabriella; Lewaherilla, Norisca (Jambura Journal of Probability and Statistics, 2024)
The aim of this research is to compare the performance of the Holt type double exponential smoothing method and the double moving average method to predict the number of poor people in Maluku Province. The performance of these two forecasting methods was implemented on data on the number of poor people in Maluku Province from 2010 to 2021. The Holt type double exponential smoothing method and the double moving average method are often used as forecasting tools for non-stationary, non-seasonal and trend data types because they have The best level of accuracy is for time series data such as data on the number of poor people in Maluku Province. The results of a comparative analysis of the performance of the two methods based on the criteria for the smallest MAPE value, it was found that the Holt type double exponential smoothing method had better performance than the double moving average method for predicting the number of poor people in Maluku Province, producing the smallest MAPE value of 4.096. The forecast results for the number of poor people in Maluku Province for 2022 is 283.66 thousand people and for 2023 it is 276.78 thousand people.